Odpowiedzi

2009-11-29T13:18:02+01:00
A) z2-18z+81
b) 0,49-1,4w+w2
c) u2-4 2/3 u +5 4/9
d) 3-2√3v+v2
e) 9y2-4,5y+9/16
f) 1,21-0,66x+0,09x2
g) 49p2-126pr+81r2
i) 10m2-2√50mn+5n2
14 3 14
2009-11-29T13:18:47+01:00
A)(z-9)(z-9)
b)(0,7-w)(0,7 -w)
d)(√3-v)(√3-v)
e) (3y -¾)(3y -¾)
f) 1,1 - 0,3x)(1,1- o,3)
g)(7p-9r)(7p - 9 r)
i) )(√10m-√5n))(√10m-√5n)
28 1 28
Najlepsza Odpowiedź!
2009-11-29T13:29:15+01:00
A) (z-9)²=z²-2*z*(-9)+9²=z²+18z+81
b) (0,7-w)²=0,7²-2*(0,7)*(-w)+w²=0,49+1,4w+w²
c) (u-2⅓)²=u²-2*u*(-2 1/3)+(2 1/3)²=u²+4 1/3u+4 1/9
d) (√3-v)²=(√3)²-2*√3*(-v)+v²=3+2√3v+3=6+2√3
e) ( 3y-¾)²=6y²-2*3y*(-3/4)+(3/4)²=6y²+9/2y+9/16
f) (1,1-0,3x)²=1,1²-2*1,1*(-0,3x)-(0,3)²=1,21+0,66x+0,09x²
g) (7p-9r)²=14p²-2*7p*(-9r)+(-9r)²=14p²+126pr+81r²
h) (√10m-√5n)²=(√10m)²-2*√10m*(-5n)+(√5n)²=10m²-10√10mn+5n²
11 3 11